2016
DOI: 10.21608/ajfm.2016.18552
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Outcome of Acutely Intoxicated Patients Admitted To Intensive Care Unit in Mansoura-Dakhlia Governorate-Egypt

Abstract: Acute poisoning is a frequent cause of admission to emergency departments and intensive care units, as it is considered as an important medical emergency requiring early diagnosis and rapid initiation of therapy. The aim of the present study was to assess characteristics, and outcomes of acutely intoxicated patients who were admitted to ICU. Also, design a scoring system regarding priority for ICU admission. The present study was carried out on 40 patients who were admitted to intensive care unit of El Mansour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…El‐Sarnagawy and Hafez 53 also identified GCS of ≤8 on admission as the most sensitive (100%) predictor for mechanical ventilation in drug‐overdosed patients. Moreover, many studies demonstrated the prognostic value of the GCS, heart rate, SBP, and respiratory rate in predicting outcomes of the ICU admitted poisoned patients 16,29,54 …”
Section: Discussionmentioning
confidence: 99%
“…El‐Sarnagawy and Hafez 53 also identified GCS of ≤8 on admission as the most sensitive (100%) predictor for mechanical ventilation in drug‐overdosed patients. Moreover, many studies demonstrated the prognostic value of the GCS, heart rate, SBP, and respiratory rate in predicting outcomes of the ICU admitted poisoned patients 16,29,54 …”
Section: Discussionmentioning
confidence: 99%
“…The age group 16-30 years old was most affected. Similar studies have confirmed the vulnerability of young people to poisons (Achour et al, 2011;Arulmurugan et al, 2017;Chen et al, 2010;Gupta et al, 1998;Oreby et al, 2016). Nevertheless, in a study carried out between 1999 and 2008 in Taiwan, aged males above 65 years old were the most affected group with medicinal drug poisoning (Chien et al, 2011).…”
Section: Discussionmentioning
confidence: 72%
“…Dog bite and food poisoning were at the top position, followed by alcohol. In similar studies, common poisoning agents were agricultural inputs, alcohol and drugs (Chen et al, 2010;Oreby et al, 2016;Saravi, 2013). Alcohol abuse is a common issue in the modern society.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Zaghary et al [25] showed that the mean value of heart rate in non-survived poisoned cases was 96.0 ± 26 beats/minute and also observed absence of significant difference between survivors and non-survivors. Contrary to this, Yu et al [5] and Oreby et al [26] noted statistically significant differences between survivors and non-survivors regarding the heart rate.…”
Section: Discussionmentioning
confidence: 81%